Type of Crime Committed as a Directive to Enforce Imprisonment against Persons Convicted of Alimony Evasion (Archives of Criminology, 2008)
In the article, the author takes a deeper look at the impact that the type of crime committed has on the classification of convicts, with particular consideration given to the crime of evading alimony. Moving on to the classification, the author elaborates on the content of Article 82 § 1 of the Code of Criminal Procedure and an assessment of decisions affecting the proper classification of convicts. Stefan Lelental devotes a separate place in the text to the meaning of the phrase ‘type of offence committed’, which, according to him, takes a narrow view of the problem and thus identifies small groups of convicted offenders for whom this phrase may be used (e.g. offenders against sexual freedom and decency or so-called dangerous offenders). Furthermore, the author of the study emphasises that increased protection of society and security of the prison do not fall within the statutory principles of classifying convicts. However, Lelental’s main goal is to prove that those convicted of the crime of failing to pay alimony should serve their prison sentence in a way that ensures the protection of the family. To this end, he presents and discusses statistical data on offences against the family and guardianship (Articles 206–211 of the Criminal Code) ascertained in the years 1999–2007 and the number of convicted offenders for offences against the family and guardianship (Articles 206–211 of the Criminal Code) between 1999 and 2006. Moreover, the text includes quantitative data on persons detained and convicted of offences against the family and guardianship (Articles 206–211 of the Penal Code) and incarcerated in penitentiaries between 1999 and 2007. In conclusion, the author notes that even in the case of paid employment, for all those convicted of the crime of failing to pay alimony, the remuneration is insufficient to satisfy the claims of the victims. According to the author, decriminalisation of non-payment of alimony could contribute to reducing overcrowding in prisons and detention centres.